AN ANALYSIS OF THE COROT’S LANDSCAPE PAINTINGS TO ENHANCE STUDENTS’ CREATIVITY AND INNOVATION IN ART EDUCATION ALIGNED WITH SUSTAINABLE CITIES AND COMMUNITIES - Burapajatana, Jaipak; Guan, Yufei; wichairat, Narong; mahaniyom, Sobsun; Phoopraser, Praphatsorn; Danila, Dabrarodni (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study investigates the artistic methods of Jean-Baptiste-Camille Corot and their application in promoting creativity and innovation in art education aligned with sustainable cities and communities. Using a mixed-method approach—including literature review, questionnaires, interviews, and artwork analysis the research was conducted with teachers and students from the Painting Program at Guizhou Qian Nan Institute of Science and Technology. Findings indicate that reconstructing Corot’s creative process effectively bridges the gap between technical training and creative development. His distinctive “silver-gray tone” and atmospheric perspective exemplify artistic innovation within structured boundaries, encouraging expressive and reflective learning. Research has found that Corot's "memory reconstruction" teaching method has established a complete paradigm for art education. The study proposes strategies to integrate traditional artistic heritage with innovative teaching models, supporting the cultivation of creative thinking and sustainable development in contemporary art education.